Tradisi Sou Lavite Dalam Perkawinan Adat Negeri Haruru Kabupaten Maluku Tengah - Waelaruno, Delza; Matitaputty, Jenny; Pattiasina, johan (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2022)
Culture and its existence can be observed in Indigenous communities across Indonesia in general, and more specifically in traditional villages in Maluku, where customary laws and practices are still strongly upheld and practised in community life, including in marriage ceremonies. One particularly interesting and still-practiced traditional marriage ceremony in Haruru Village is the sou lavite (sarong and clothing). The issues addressed in this paper are: How is the sou late tradition carried out? What is the meaning behind the sou lavite tradition? And what values are embedded in the sou lavite tradition? The research method used is qualitative, with data collection techniques including literature review, observation, and interviews. Data analysis begins with data collection, followed by data reduction, data presentation, and conclusion drawing. The results show that the sou late tradition is divided into three important stages: the preparation stage, the implementation stage, and the final stage. The preparation stage is further divided into two key processes: nok and editing. The implementation stage involves several steps: sopa adat, sarong parking, so sauna, and lesa sou lavite. The final stage of the sou late tradition involves prayers and the handing over of a black garment to the groom's sister.